2002
DOI: 10.1136/jcp.55.10.749
|View full text |Cite
|
Sign up to set email alerts
|

Detection of campylobacter species: a comparison of culture and polymerase chain reaction based methods

Abstract: Aims: To investigate the optimal method for the detection of campylobacters from stool samples by comparing selective culture with membrane filtration and the polymerase chain reaction (PCR). Methods: Three hundred and forty three stool samples were investigated by each of the three methods mentioned above. Selective culture was performed with charcoal cefoperazone desoxycholate agar plates. Membrane filtration was performed using cellulose triacetate membranes with 0.45 µm pores placed on blood agar plates. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 29 publications
(19 reference statements)
4
78
0
2
Order By: Relevance
“…The results, which reveal a significant proportion of PCR-positive but culture-negative specimens were consistent with many other studies (Logan, et al 2001, Gentry-Weeks, et al 2002, Kulkarni, et al 2002. Taken together with the epidemiological data presented in the present study, supported the view that PCR-based testing is more sensitive than conventional culture for the detection of enteric bacterial pathogens in stool samples.…”
Section: Journal Of Biology and Life Sciencesupporting
confidence: 81%
“…The results, which reveal a significant proportion of PCR-positive but culture-negative specimens were consistent with many other studies (Logan, et al 2001, Gentry-Weeks, et al 2002, Kulkarni, et al 2002. Taken together with the epidemiological data presented in the present study, supported the view that PCR-based testing is more sensitive than conventional culture for the detection of enteric bacterial pathogens in stool samples.…”
Section: Journal Of Biology and Life Sciencesupporting
confidence: 81%
“…The rates of detection of S. enterica and C. jejuni improved by 15% to 18%. Previous studies have also shown improvements in the rates of detection of gastrointestinal pathogens (7,17,22,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…At least one week before sampling, broilers had not been treated with antimicrobial agents prior to sample collection. Campylobacter isolation and identification has previously been described by membrane filtration technique [24]. Briefly, the swabs were incubated in Preston broth (Nutrient broth no.2) (Oxoid, Hampshire, England) containing 5% lysed horse blood, Campylobacter growth supplement and modified Preston selective supplement (2500 IU of polymyxin B, and 5 mg each of rifampicin, trimethoprim and amphotericin B) (Oxoid, Hampshire, England) for 24 hr or overnight at 37C.…”
mentioning
confidence: 99%